2021
DOI: 10.5935/1980-6906/eptpc1913664
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies in health professionals facing Covid-19: A systematic review

Abstract: No momento em que escrevo este editorial, o Brasil (e o mundo) atravessam um doloroso ressurgimento da Covid-19. Não refeitos dos seus múltiplos impactos negativos -especialmente em termos de saúde mental -, somos novamente chama-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 0 publications
3
7
0
4
Order By: Relevance
“…In terms of coping strategies of residents to reduce these general, direct and indirect negative impacts, we identified two strategies including positive coping strategies (precautionary activities stress release activities), and negative coping strategies (obsessivecompulsive behaviors, travel anxiety, and harmful and negative behavior). The current survey is similar to Vally (2020), Dullius et al (2021), Hidalgo-Andrade et al ( 2021), Fluharty and Fancourt (2021) and Girma et al (2021) studies. For example, Dullius et al (2021) showed that the key coping strategies of health experts against COVID-19 were being supported from family and relatives, colleagues, organizations, etc., religious belief, and doing hobbies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In terms of coping strategies of residents to reduce these general, direct and indirect negative impacts, we identified two strategies including positive coping strategies (precautionary activities stress release activities), and negative coping strategies (obsessivecompulsive behaviors, travel anxiety, and harmful and negative behavior). The current survey is similar to Vally (2020), Dullius et al (2021), Hidalgo-Andrade et al ( 2021), Fluharty and Fancourt (2021) and Girma et al (2021) studies. For example, Dullius et al (2021) showed that the key coping strategies of health experts against COVID-19 were being supported from family and relatives, colleagues, organizations, etc., religious belief, and doing hobbies.…”
Section: Discussionsupporting
confidence: 89%
“…The current survey is similar to Vally (2020), Dullius et al (2021), Hidalgo-Andrade et al ( 2021), Fluharty and Fancourt (2021) and Girma et al (2021) studies. For example, Dullius et al (2021) showed that the key coping strategies of health experts against COVID-19 were being supported from family and relatives, colleagues, organizations, etc., religious belief, and doing hobbies. Hidalgo-Andrade et al ( 2021) also showed being socially supported, doing exercise, and taking part in recreational activities are the most applicable coping strategies when faced with stress related to online teaching.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Trazendo a questão para a atualidade com a pandemia, ressalta-se que um tratamento mais humanizado, com a participação da família, amigos e instituições, possibilitou uma melhor recuperação de pacientes acometidos por COVID-19 em todos os seus aspectos quando comparado aos tratamentos e cuidados visando apenas o fim, ou seja, a recuperação final do paciente 21 .…”
Section: Perspectivas Filosóficas E Modos De Cuidado Em Saúde Pública...unclassified